Prospective and positive mental imagery deficits in dysphoria. - Holmes, E; Lang, T; Moulds, M; Steele, A (2008)
We know less about positive mental imagery than we do about negative mental imagery in depression. This study examined the relationship between depressed mood and the subjective experience of emotion in imagined events; specifically, prospective imagery, and imagery in response to emotionally ambiguous stimuli. One hundred and twenty-six undergraduates completed measures of depression, imagery vividness for future events, and a homograph interpretation task in which they generated images and subsequently rated image pleasantness and vividness. As predicted, compared to low dysphoria, high dysphoria was associated with poorer ability to vividly imagine positive (but not negative) future events. These findings were augmented by the observation that high dysphorics provided lower pleasantness ratings of images generated in response to homographs they interpreted as positive. We suggest that an imbalance in the inability to vividly imagine positive but not negative future events may curtail the ability of high dysphorics to be optimistic. High dysphoric individuals are further disadvantaged: even when they interpret ambiguity positively, the resulting images they generate are associated with less positive affect. Therapeutic strategies that address both such positive-specific imagery biases hold promise for depression treatment innovation.